2017
DOI: 10.1186/s12014-017-9167-8
|View full text |Cite
|
Sign up to set email alerts
|

Serum protein pattern associated with organ damage and lupus nephritis in systemic lupus erythematosus revealed by PEA immunoassay

Abstract: BackgroundSystemic lupus erythematosus (SLE) is a remarkably heterogeneous autoimmune disease. Despite tremendous efforts, our knowledge of serum protein patterns in severe SLE phenotypes is still limited. We investigated the serum protein pattern of SLE, with special emphasis on irreversible organ damage and active lupus nephritis (LN) as assessed by renal Systemic Lupus Erythematosus Disease Activity Index.MethodsWe used proximity extension immunoassay (PEA, Proseek Multiplex, Olink) to assess the serum leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 69 publications
2
16
0
Order By: Relevance
“…IL-18 has also been suggested as a potential predictive biomarker for long-term outcomes in pediatric LN ( 23 ). Renal disease is a major predictor of damage progression in SLE, and our findings of a near-significant association of IL-18 with organ damage in multivariable analysis ( p = 0.07) are supported by previous findings in a smaller study which reported increased serum IL-18 in SLE patients with organ damage ( 53 ). Furthermore, we observed that high baseline serum IL-18 levels were associated with the presence of organ damage at the subsequent visit, suggesting a potential for serum IL-18 as a predictive biomarker for irreversible organ damage.…”
Section: Discussionsupporting
confidence: 90%
“…IL-18 has also been suggested as a potential predictive biomarker for long-term outcomes in pediatric LN ( 23 ). Renal disease is a major predictor of damage progression in SLE, and our findings of a near-significant association of IL-18 with organ damage in multivariable analysis ( p = 0.07) are supported by previous findings in a smaller study which reported increased serum IL-18 in SLE patients with organ damage ( 53 ). Furthermore, we observed that high baseline serum IL-18 levels were associated with the presence of organ damage at the subsequent visit, suggesting a potential for serum IL-18 as a predictive biomarker for irreversible organ damage.…”
Section: Discussionsupporting
confidence: 90%
“…has been reported earlier. Their association with organ damage has also been documented [44]. A similar finding in pregnant lupus patients hints to an increase in susceptibility to different organ complications, particularly to lupus nephritis.…”
Section: Discussionmentioning
confidence: 60%
“…The protein levels of molecules associated with inflammation and osteoclastogenesis (see S1 Table) were assessed on a 92-plex Targeted Proteomics Chip (Proseek Multiplex Oncology I kit, Olink Bioscience, Uppsala, Sweden) using 1 μl of tissue lysates as reported previously [26, 27]. For sensitivity and specificity parameters, see Assarsson et al [28].…”
Section: Methodsmentioning
confidence: 99%